2017
DOI: 10.1007/s40265-017-0782-5
|View full text |Cite|
|
Sign up to set email alerts
|

Durvalumab: First Global Approval

Abstract: Intravenous durvalumab (Imfinzi™; AstraZeneca) is a fully human monoclonal antibody that blocks programmed cell death ligand-1 binding to its receptors (PD-1 and CD80), resulting in enhanced T-cell responses against cancer cells. The US FDA has granted durvalumab accelerated approval for the treatment of patients with locally advanced or metastatic urothelial carcinoma who have disease progression during or following platinum-containing chemotherapy, or within 12 months of neoadjuvant or adjuvant platinum-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 22 publications
3
92
0
2
Order By: Relevance
“…The Oncologist 2020;25: [94][95][96][97][98] Immunotherapy in the form of checkpoint blockade has resulted in impressive responses for several previously refractory tumor types. Indeed, the U.S. Food and Drug Administration (FDA) has now approved seven checkpoint inhibitors: pembrolizumab, nivolumab, durvalumab, avelumab, atezolizumab, cemiplimab, and ipilimumab [1][2][3][4][5][6][7]. Immune checkpoint inhibitors mediate responses by reactivating the immune system.…”
mentioning
confidence: 99%
“…The Oncologist 2020;25: [94][95][96][97][98] Immunotherapy in the form of checkpoint blockade has resulted in impressive responses for several previously refractory tumor types. Indeed, the U.S. Food and Drug Administration (FDA) has now approved seven checkpoint inhibitors: pembrolizumab, nivolumab, durvalumab, avelumab, atezolizumab, cemiplimab, and ipilimumab [1][2][3][4][5][6][7]. Immune checkpoint inhibitors mediate responses by reactivating the immune system.…”
mentioning
confidence: 99%
“…To date, six monoclonal antibodies targeting the PD-1/PD-L1 pathway have been approved by the US FDA for clinical use; among such antibodies, pembrolizumab, nivolumab, and cemiplimab are anti-PD-1 antibodies [209,210], whereas durvalumab, atezolizumab, and avelumab are anti-PD-L1 antibodies [211]. Tumeh et al [212] analyzed samples from patients with melanoma in the phase I clinical trials of pembrolizumab and found that the CD8 T cell density at the tumor site was significantly lower in patients who did not respond to pembrolizumab compared with that of patients who responded to pembrolizumab.…”
Section: Combinations Of Ovs and Pd-1/pd-l1 Blockadementioning
confidence: 99%
“…Durvalumab (MEDI4736) is a human IgG1 κ monoclonal antibody against PD‐L1. It blocks the interaction of PD‐L1 with PD‐1 and CD80 molecules . Based on DANUBE (NCT02516241), BISCAY (NCT02546661), and study 10 (NCT02261220) results, FDA, on 1 May 2017, granted approval to durvalumab as second‐line therapy for patients with locally advanced or metastatic bladder cancer whom prognosis is poor …”
Section: Immune Checkpoint Inhibitor (Ici) For Treatment Of Bladder Cmentioning
confidence: 99%